2019
DOI: 10.1126/scitranslmed.aat0852
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 augments mucosal damage in colitis

Abstract: There is a major unmet clinical need to identify pathways in inflammatory bowel disease (IBD) to classify patient disease activity, stratify patients that will benefit from targeted therapies such as anti-TNF, and identify new therapeutic targets. In this study we conducted global transcriptome analysis to identify IBD-related pathways using colon biopsies, which highlighted the coagulation gene pathway as one of the most enriched gene sets in IBD subjects. Using this gene-network analysis across 14 independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 84 publications
3
42
0
1
Order By: Relevance
“…Although the antifibrinolytic PAI-1 functions have received most of the attention in research on tissue fibrosis, 22 more recent report has demonstrated a correlation between enhanced PAI-1 expression and inflammation in IBD patients and murine acute colitis model. 11 In the present study, we ob- served PAI-1 overexpression at active lesions in both patients with CD and mice with the chronic colitis; this overexpression seems to exacerbate intestinal fibrosis and PAI-1 inhibitor is a potential drug candidate for targeted therapy. As PAI-1 inhibition induced MMP-9 activation in the TNBS colitis model, PAI-1-mediated MMP-9 activity inhibition could be a key mechanism via which ECM is deposited in the lesions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the antifibrinolytic PAI-1 functions have received most of the attention in research on tissue fibrosis, 22 more recent report has demonstrated a correlation between enhanced PAI-1 expression and inflammation in IBD patients and murine acute colitis model. 11 In the present study, we ob- served PAI-1 overexpression at active lesions in both patients with CD and mice with the chronic colitis; this overexpression seems to exacerbate intestinal fibrosis and PAI-1 inhibitor is a potential drug candidate for targeted therapy. As PAI-1 inhibition induced MMP-9 activation in the TNBS colitis model, PAI-1-mediated MMP-9 activity inhibition could be a key mechanism via which ECM is deposited in the lesions.…”
Section: Discussionmentioning
confidence: 71%
“…10 Very recently, it has been reported that PAI-1 expression was highly enriched in active lesions in both patients with IBD and mice with experimental colitis, and confirmed that PAI-1 and its direct target, tPA, played an important role in regulating intestinal inflammation. 11 However, their functions have been only validated in the acute phase of experimetal colitis and its correlation with intestinal fibrogenesis observed in the chronic phase has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The impact on mRNA metabolism also enables IL-17 to synergize with other cytokines such as TNF to amplify the inflammatory response (Chiricozzi et al, 2011). Interestingly, IL-17 has been shown to cooperate with a wide range of signaling activators, including IFN-γ, IL-13, TGF-β, and even microbial products (Fabre et al, 2014a;Hall et al, 2017;Kaiko et al, 2019;Teunissen et al, 1998;Verma et al, 2017). Such promiscuity is highly relevant but poorly understood in the context of intratumoral inflammation, which is usually driven by a myriad of factors and exhibits considerable heterogeneity, even among tumors of the same tissue origin.…”
Section: Il-17-induced Inflammatory Response and Cancermentioning
confidence: 99%
“…Statistical significance was set at FDR < 0.05. All target gene expression was calculated as log 2 intensity robust multi-array average signals (Log 2 transformed intensity value) [18,19].…”
Section: Gene Expression In Human Crc Microarray Datasetmentioning
confidence: 99%